Muon dynamic radiography of density changes induced by hydrothermal activity at the La Soufrière of Guadeloupe volcano - Jourde, Kevin (Sci Rep, 2016)
Imaging geological structures through cosmic muon radiography is a newly developed technique which shows a great potential in volcanology. Here we demonstrate that muon radiography permits to detect and characterize mass movements in shallow hydrothermal systems of low-energy active volcanoes like the La Soufrière lava dome. We present an experiment conducted on this volcano during the Summer 2014 and bring evidence that very important density changes occurred in three domains of the lava dome. Depending on their position and on the medium porosity the volumes of these domains vary from 1 × 10(6) m(3) to 7 × 10(6) m(3). However, the total mass budget remains approximately constant : two domains show a mass loss (Δm∈ [−0.8;−0.4] × 10(9) kg) and the third one a mass gain (Δm∈ [1.5; 2.5] × 10(9) kg). We attribute the negative mass changes to the formation of steam in shallow hydrothermal reservoir previously partly filled with liquid water. This coincides with the emergence of new fumaroles on top of the volcano. The positive mass change is synchronized with the negative mass changes indicating that liquid water probably flowed from the two reservoirs invaded by steam toward the third reservoir.